Pulmonary Valve Regurgitation: Neither Interventional Nor Surgery Fits All - Corno, Antonio F. (Frontiers in Pediatrics, 2018)
Introduction. PV implantation is indicated for severe PV regurgitation after surgery for congenital heart defects, but debates accompany the following issues: timing of PV implantation; choice of the approach, percutaneous interventional versus surgical PV implantation, and choice of the most suitable valve Timing of pulmonary valve implantation. The presence of symptoms is class I evidence indication for PV implantation. In asymptomatic patients indication is agreed for any of the following criteria: PV regurgitation >20%, indexed end-diastolic right ventricular volume >120–150 ml / m2 BSA, and indexed end-systolic right ventricular volume >80–90 ml / m2 BSA Choice of the approach: percutaneous interventional versus surgical. The choice of the approach depends upon the morphology and the size of the right ventricular outflow tract, the morphology and the size of the pulmonary arteries, the presence of residual intra-cardiac defects and the presence of extremely dilated right ventricle Choice of the most suitable valve for surgical implantation. Biological valves are first choice in most of the reported studies. A relatively large size of the biological prosthesis presents the advantage of avoiding a right ventricular outflow tract obstruction, and also of allowing for future percutaneous valve-in-valve implantation. Alternatively, biological valved conduits can be implanted between the right ventricle and pulmonary artery, particularly when a reconstruction of the main pulmonary artery and/or its branches is required. Hybrid options: combination of interventional and surgical. Many progresses extended the implantation of a PV with combined hybrid interventional and surgical approaches. Major efforts have been made to overcome the current limits of percutaneous PV implantation, namely the excessive size of a dilated right ventricular outflow tract and the absence of a cylindrical geometry of the right ventricular outflow tract as a suitable landing for a percutaneous PV implantation. Conclusion. Despite tremendous progress obtained with modern technologies, and the endless fantasy of researchers trying to explore new forms of treatment, it is too early to say that either the interventional or the surgical approach to implant a PV can fit all patients with good long-term results.